Pengaruh Pendapatan Pegadaian, Jumlah Nasabah, Harga Emas Dan Inflasi Terhadap Penyaluran Pembiayaan Rahn - Heidy Paramitha Devi; Richo Diana Aviyanti (INVENTORY: JURNAL AKUNTANSI, 2023)
This study uses secondary data in the form of pawnshop revenue, number of customers, and distribution of rahn financing accessed from the financial reports of PT. Pegadaian (Persero) Indonesia for 2016-2020on Statistics for Indonesian Special Financial Institutions issued by the Financial Services Authority (OJK) as well as data on gold prices and inflation rates during the 2016-2020period. Data analysis techniques use the classical assumption test, multiple linear regression analysis, and hypothesis testing (Statistic t test/Partial test, F/Simultaneous test, and Coefficient of Determination test). The results show that partially pawnshop revenue, number of customers, gold price and inflation affect the distribution of rahn financing at Sharia Pawnshops in Indonesia for the 2016-2020  period and simultaneously pawnshop income, number of customers, gold price and inflation affect the distribution of rahn financing at Pawnshops Sharia in Indonesia for the 2016-2020  period. As for the coefficient of determination of 93.28% percent, while the remaining 6.72% is explained by other variables not examined in this study.